2014
DOI: 10.1007/s12031-014-0438-9
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effects of Poly (butyl) Cyanoacrylate Nanoparticles Containing Vasoactive Intestinal Peptide Against 6-Hydroxydopamine-Induced Neurotoxicity In Vitro

Abstract: The present study investigated brain delivery system of vasoactive intestinal peptide (VIP) adsorbed on poly (butyl cyanoacrylate) nanoparticles coated with polysorbate 80 (P80-poly (butyl) cyanoacrylate (PBCA)-nanoparticles (NPs)) and the neuroprotective effects on the formulation in the model of 6-hydroxydopamine (6-OHDA)-induced Parkinsonian dysfunction in the human neuroblastoma cell line SH-SY5Y. Drug-loaded nanoparticles were prepared by emulsion polymerization method using VIP and PBCA and then stirring… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…Several factors contribute to the high entrapment efficiency of propolis (near 90%) into the PBCA-NP, including high solid-state solubility of drug/substance in the polymer, the solubility of drugs in the aqueous phase, and the fast rate of precipitation of the polymer in the organic phase. Additionally in this experiment, polymer–surfactant aggregates might be formed at higher surfactant concentrations minimizing the solubility of the drug into the aqueous phase ( Xu et al, 2015 ). Studies of propolis release kinetics at different pH values in PBS, showed an initial burst release within the first 6 h, which may be associated with the distribution of a small amount of propolis from the surface of the PBCA-NP.…”
Section: Discussionmentioning
confidence: 99%
“…Several factors contribute to the high entrapment efficiency of propolis (near 90%) into the PBCA-NP, including high solid-state solubility of drug/substance in the polymer, the solubility of drugs in the aqueous phase, and the fast rate of precipitation of the polymer in the organic phase. Additionally in this experiment, polymer–surfactant aggregates might be formed at higher surfactant concentrations minimizing the solubility of the drug into the aqueous phase ( Xu et al, 2015 ). Studies of propolis release kinetics at different pH values in PBS, showed an initial burst release within the first 6 h, which may be associated with the distribution of a small amount of propolis from the surface of the PBCA-NP.…”
Section: Discussionmentioning
confidence: 99%
“…In our previous study, polybutylcyanoacrylate nanoparticles (PBCA NP) was used as a polymeric colloidal vector for brain-derived neurotrophic factor (BDNF) gene transfection and BDNF protein delivery; uptake of these agents by mouse induced pluripotent stem cells (iPSCs) resulted in neural-lineage-committed cells in as short as 7 days [15,16]. The biocompatible and biodegradable nature of PBCA NPs, as well as central nervous system targeting capabilities, conferred by polysorbate 80 (PS80) coating, makes it ideal as a delivery system for drugs, peptides, proteins, and genes into the central nervous system [17][18][19]. PBCA NPs can be synthesized under ambient conditions using scalable emulsion polymerization of n-butylcyanoacrylate monomers or nano-precipitation of pre-formed PBCA polymers [20], and the cargo can either be carried by surface adsorption on pre-formed nanoparticles or be encapsulated within the nanoparticle during its synthetic process.…”
Section: Introductionmentioning
confidence: 99%
“…The tween 80 (T80)-coated polybutylcyanoacrylate nanoparticle (PBCA NP) is a versatile polymeric delivery system that exhibits CNS-targeting capabilities [31,32], and it has been widely studied for the delivery of various substances, including drugs, proteins, and peptides, and genes that are normally impermeable to the BBB into the CNS [33,34,35,36]. The cargos can either be carried by surface adsorption or encapsulation using the easily scalable polymerization or nano-precipitating methods under ambient conditions with the n-butylcyanoacrylate (BCA) monomer or pre-formed PBCA polymers, respectively [37].…”
Section: Introductionmentioning
confidence: 99%